2012
DOI: 10.1007/s00405-012-2070-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in chronic otitis media

Abstract: Chronic otitis media usually presents with a benign tumor-like lesion of the temporal bone known as a cholesteatoma. The role of oxidative stress in the pathogenesis of chronic otitis media and cholesteatoma has not yet been fully explored. Therefore, the aim of this study was to investigate the oxidative stress markers and antioxidant enzymes in patients with cholesteatomatous and noncholesteatomatous chronic otitis media and in healthy subjects. A prospective controlled trial was performed on cholesteatomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 34 publications
4
41
0
2
Order By: Relevance
“…Moreover, Aksoy et al revealed an association of patients with allergic rhinitis to increased serum protein oxidation levels (Aksoy et al 2009(Aksoy et al , 2012. Other fi ndings add to the evidence that elevated serum oxidant levels and declined antioxidant status levels were observed in patients with chronic long-term otitis media (Garca et al 2013a ;Baysal et al 2013 ;Testa et al 2012 ).…”
Section: Select Misconceptions In Free-radical Biologymentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, Aksoy et al revealed an association of patients with allergic rhinitis to increased serum protein oxidation levels (Aksoy et al 2009(Aksoy et al , 2012. Other fi ndings add to the evidence that elevated serum oxidant levels and declined antioxidant status levels were observed in patients with chronic long-term otitis media (Garca et al 2013a ;Baysal et al 2013 ;Testa et al 2012 ).…”
Section: Select Misconceptions In Free-radical Biologymentioning
confidence: 79%
“…Truly reactive radicals are those chemical species with one or two highly reactive unpaired valence electrons in open electron shell(s). A large body of evidence suggests that free radicals are linked to the pathogenesis of tumors (Manjunath et al 2010 ;Valko et al 2006 ;Dwivedi et al 2008 ), hearing loss (Yamasoba et al 2013 ;Rewerska et al 2013 ), tonsillitis (Garca et al 2013b ;Cvetkovic et al 2009 ;Yilmaz et al 2004 ;Li et al 2011 ), allergic rhinitis (Aksoy et al 2009(Aksoy et al , 2012, chronic otitis media (Garca et al 2013a ;Baysal et al 2013 ;Testa et al 2012 ), and rhinosinusitis (Citardi et al 2006 ;Uslu et al 2003 ) and implies that antioxidant therapy eventually may be employed as a strategy to ameliorate these disorders and diseases (Ding et al 2013 ;Tian et al 2013 ;Someya et al 2010 ). As has been shown recently, however, many antioxidants that are effective in animal models are not effective in human clinical trials.…”
Section: Overview and Introductionmentioning
confidence: 98%
“…Cells undergoing p21-induced apoptosis presented higher sensitivity to oxidants (24). Recently Baysal et al (25) reveal that in cholesteatoma cases, the oxidative stress and antioxidant enzyme imbalance is significant. We may suspect some correlation between p21-induced apoptosis and oxidative stress in cholesteatoma.…”
Section: Discussionmentioning
confidence: 98%
“…This whole antioxidant defense in the body is defined as the TAC, which is in balance with oxidants in the healthy organism. In recent years, to determine the oxidative balance, serum TAC, a reliable parameter in the evaluation of antioxidant capacity, has been measured (Baysal et al 2013). …”
Section: Discussionmentioning
confidence: 99%